Mincer Earnings Functions for the Netherlands 1962-2012 - Joop Hartog; Sander Gerritsen (Center for Economic Studies and ifo Institute (CESifo), 2016)
We extract estimation results on the Mincer earnings function from four earlier studies and add new results from a recent dataset. We analyse differences related to differences in earnings concepts, in sampling frame and differences among studies that cannot be explained. Jointly, the studies show a clear U-shaped development in the rate of return to education from 1962 to 2012, with a bottom in the 1980's. We explain this from Tinbergens's race between suppy and demand (schooling and technology) and suggest this may be a widespread international pattern. Returns to potential experience show no marked time trend.
Keywords: I26; J24; J31; 330; returns to education; Mincer earnings equation; race supply and demand